Experimental characteristics of lost fast negative ions on EAST tokamak - Z.X. Zhang; J. Huang; J.F. Chang; C.R. Wu; J. Galdon-Quiroga; A. Snicker; M. Isobe; K. Ogawa; K.Y. He; S.S. Wang; Y.X. Sun; X.H. Wang; et al. (Nuclear Fusion)
It is the first time that fast negative-ion loss signals are observed by Fast-ion Loss Detector (FILD) and analyzed in EAST neutral beam injection experiment. Velocity-space distributions of lost fast negative and positive ions reconstructed by the FILDSIM code are basically consistent. Orbit analysis backtracked by the ASCOT code shows that the fast negative ions are generated at the low-field side (LFS) scrape-off layer, whereas the fast positive ions are generated near the last closed flux surface (LCFS) at both the high- and LFSs. The existence of fast negative-ion loss indirectly suggests a very high neutral particle density near both the main limiter and antenna limiter. The differing birth locations of fast positive and negative ions result in distinct loss behaviors during ELM H-mode and n = 3 rotating RMP experiments. The asymmetry of neutral particle density in tokamak suggest that previous studies may have underestimated the fraction of charge exchange (CX) losses due to the assumption of a uniform neutral particle density outside the LCFS. Therefore, simulations evaluating the CX loss fraction in the future should account for a three-dimensional distribution of neutral particle density, including local gas puffing and the neutral particle density around various limiters.